Hawthorne a life - Wineapple, Brenda (A Borzoi book, 2003)
Hawthorne himself declared that he was not "one of those supremely hospitable people who serve up their own hearts, delicately fried, with brain sauce, as a tidbit" for the public Yet those who knew him best often took the opposite position. "He always puts himself in his books," said his sister-in-law Mary Mann, "he cannot help it." His life, like his work, was extraordinary, a play of light and shadow. [In this volume, the author] navigates the high tides and chill under-currents of Hawthorne's life ... In him, the quest of his generation for an authentically American voice bears disquieting fruit.-Dust jacket.